COVID-19 Outbreak Prediction using Additive Time Series Forecasting Model - Gull, Karuna; Kanakaraddi, Suvarna; Chikaraddi, Ashok (Trends in Sciences, 2022)
It is no secret that COVID-19 is a hot topic these days. Its spread has engulfed the world. People all throughout the world have suffered because of it. A unique coronavirus epidemic that has swept throughout the globe is examined and analysed in this article. COVID-19 outbreaks in various places are analysed using machine learning models, which are visualised using charts, tables, graphs and predictions depending on the available data. For prediction models, the time series forecasting package (PROPHET) is utilised as part of machine learning. The work done may aid in the development of some novel concepts and ways that can be utilised as recommendations to prevent the spread of COVOD-19. GRAPHICAL ABSTRACT